Efektivitas Sosialisasi Hukum dalam Mengurangi Kenakalan Remaja di Kecamatan Cibeber - Elgi Aris Munandar; Muhamad Yopi; Wantia Sinta Anggraini; Tiara Nofiana; Slamet Gunadi; Yolla Sukma Handayani; Asih Setyo Rini (Institut Teknologi dan Bisnis Semarang, 2024)
This service explores the relationship between social media use and juvenile delinquency, one of which is promiscuity in the digital era with a focus on the impact of socialization involving the police. Through outreach programs, researchers seek to provide understanding to teenagers about the risks associated with using social media and how to avoid delinquent behavior. This research found that effective socialization can reduce the level of juvenile delinquency by increasing their awareness of the negative impacts of social media. The research results also show the importance of collaboration between parents and law enforcement in educating teenagers how to use social media wisely.